Adaptive dynamic pattern of alternative educational institution in Java, Indonesia - Fahmi MR, Moh Irsyad; Widiastuti, Anik; Widodo, Syukri Fathudin Achmad; Marhumah, Marhumah; Jaya, Pajar Hatma Indra (International Journal of Evaluation and Research in Education (IJERE), 2025)
Alternative educational institutions in Indonesia deal with significant problems in maintaining their unique pedagogical approaches, meeting regulatory requirements and societal expectations. This study addresses the problem of balancing institutional autonomy with systemic integration by introducing the adaptive dynamic of alternative education (ADAE) pattern. Using a qualitative approach, data was collected through two focus group discussions (FGDs) with purposively selected participants representing three distinct alternative education institutions: Tanoker in East Java, Komunitas Belajar Qaryah Thayyibah (KBQT) in Central Java, and Sekolah Alam Sukahaji in West Java. The sample comprised 12 participants (3 institution heads and 9 teachers) chosen based on their understanding of their respective institution’s social situations. Additionally, two education experts with expertise in mainstream and alternative education were interviewed. The findings of the study reveal that ADAE is built on three integrated philosophical pillars: theomorphic, eduhumanistic, and futuristic. The pattern demonstrates how alternative educational institutions navigate between autonomy and integration through dynamic positioning influenced by external and internal factors. The research found the practical implications include a framework for alternative institutions that implementation of ADAE enables institutions to maintain their innovative practices, achieving legitimacy through measurable community impact.